Social media addiction and young people: a systematic review of literature - Xuan, Yap Jing; Che Amat, Muhammad Asyraf (SynthesisHub Advance Scientific Research, 2020)
Background: In this era, social media addiction is prevalent among young people. Several approaches had been widely use among young people but it’s superficial. The relationship between social media addiction and young people should be investigated before designing the most suitable and symptomatically approach to prevent the addiction among youngsters. Objective: The systematic review aims to review and synthesise the factors, relationship between young people and social media addiction and intervention of social media addiction among young people. Design: A systematic review was designed based on the PRISMA, an evidence-based minimum set of items for reporting in systematic reviews and meta-analyses. Data Sources: Articles published between year 2010 to 2020 were sought from SCOPUS and Science Direct. Methods: All related papers were reviewed and quality evaluation was performed. Eleven studies were finally selected and data were extracted, organized and analysed in narrative synthesis. Results: The need of satisfaction in real-life relationship among young people become the most common factors of addiction, addiction to social media will caused mental health problem among them indirectly and cognitive reconstruction and strategies may help in rehabilitation. Conclusion: Counsellors as well as mental health workers have to equip relevant knowledge in social media addiction to provide the most effective services to young people with social media addiction.